Comparative Studies Of Fuzzy Logic Base Power System Stabilizers In Enhancing Dynamic Stability Of A Generator Connected To Infinite Bus - Hayfaa, Mohammed Hussein Hasan; Marizan, Sulaiman; Mohammed Rasheed, Jubair Al-Hiealy; Rosli, Omar; Mohd Shahrieel, Mohd Aras (IDOSI Publications, 2016)
Power system stabilizers (PSS) are added to excitation system to enhance the damping during low frequency oscillations. This paper presents a study of fuzzy logic power system stabilizer for stability enhancement of a single machine connected to infinite bus (SMIB) power system. Recently fuzzy logic as a novel robust control design method has shown promising results. The emphasis in fuzzy control design center is around uncertainties in the system parameters and operating conditions. Fuzzy logic controller (FLC) has been suggested as a possible solution to overcome this problem, thereby using linguist information and avoiding a complex system mathematical model, while giving good performance under different operating conditions. The proposed approach is found to have stable convergence characteristics and resulted in good voltage regulation and damping characteristics. The stabilizing signals were computed using the fuzzy membership functions with variations of angular speed and acceleration as the inputs. The simulations were tested under different operating conditions, with different membership functions using MATLAB /SIMULINK. The simulation results are quite encouraging and satisfactory.